1999
DOI: 10.1017/s0142716499003033
|View full text |Cite
|
Sign up to set email alerts
|

Literacy attainment in a second language submersion context

Abstract: The purpose of this study was to describe the first and second language literacy levels of a sample of 222 Turkish children living in the Netherlands and to identify the factors that are related to individual variation in their literacy performance. Measures of both school literacy and functional literacy were taken in the target languages, Turkish and Dutch. Data of monolingual control groups were used as benchmarks. To explore individual variation in biliteracy scores, background characteristics originating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 24 publications
2
42
1
2
Order By: Relevance
“…However, like their parents, they were mostly from low socio-economic backgrounds with a lack of rich and elaborate linguistic input from their parents (Leseman and van den Boom 1999). Given all of these factors, they tended to fall behind their peers in education (Aarts and Verhoeven 1999;Leseman 2000;Verhallen and Schoonen 1998). Considering the role of parents in children's school achievement, and given that second-generation families are an under-researched group, a main question arises regarding how second-generation families, who were raised as bilingual by monolingual parents, shape their home language interaction with their third-generation children.…”
Section: Profile Of the Turkish Community In The Netherlandsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, like their parents, they were mostly from low socio-economic backgrounds with a lack of rich and elaborate linguistic input from their parents (Leseman and van den Boom 1999). Given all of these factors, they tended to fall behind their peers in education (Aarts and Verhoeven 1999;Leseman 2000;Verhallen and Schoonen 1998). Considering the role of parents in children's school achievement, and given that second-generation families are an under-researched group, a main question arises regarding how second-generation families, who were raised as bilingual by monolingual parents, shape their home language interaction with their third-generation children.…”
Section: Profile Of the Turkish Community In The Netherlandsmentioning
confidence: 99%
“…Most research has concentrated on the Dutch language skills of Turkish children compared to their native Dutch speaking peers. While a limited amount of research has focused on bilingual skills (Aarts and Verhoeven 1999;Driessen and Merry 2011;Leseman 2000) very few studies have investigated first language skills (Aarssen 1996;Akoglu and Yagmur 2016;Bezcioglu-Goktolga 2016;Schaufeli 1992), home language environment (i.e. Scheele, Leseman, and Mayo 2010), or language maintenance, shift, and code-switching (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Given the value attributed to lexical development, receptive and productive skills of Turkish immigrant children in Dutch vocabulary have been compared with native Dutch children in many studies. The gaps between the performance of native Dutch children and Turkish immigrant children were reported widely (Aarts and Verhoeven 1999;Dagevos, Gijsberts, and van Praag 2003;Tesser and Iedema 2001) and in almost all studies Turkish immigrant children were shown to have much lower competence compared to native Dutch children. Most researchers only measure immigrant minority children's mainstream language skills rather than their home language skills and claim language deficiency on behalf of immigrant children.…”
Section: Introductionmentioning
confidence: 98%
“…Immigrant minority languages are most often associated with problems of poverty, underachievement in schools, social and cultural problems, as well as lack of integration into the society of residence. A number of research studies have shown over and over that bilingual immigrant children have a lower proficiency in Dutch than monolingual peers have (Aarts and Verhoeven 1999;Driessen and Merry 2011;Leseman 2000). Lexical depth both in Dutch and Turkish were found to be very limited among Turkish immigrant children (Verhallen and Schoonen 1998).…”
Section: Introductionmentioning
confidence: 98%
“…For most Turkish immigrant children in The Netherlands, Turkish is their home language and school enrollment often marks their first full submersion in a primarily Dutch language environment. The special interest in this group follows from the persistent disadvantages in Dutch language and literacy development compared with native Dutch children at the start of primary school (Aarts & Verhoeven, 1999;Leseman, 2000;Leseman & De Jong, 1998;Leseman & Van den Boom, 1999;Sociaal en Cultureel Planbureau [SCP], 2007). We hypothesize that Turkish-Dutch children have more difficulty in remembering novel phonological forms in Dutch because they have less support from entrenched phonotactic knowledge of Dutch, thereby hindering their Dutch vocabulary development.…”
Section: Introductionmentioning
confidence: 99%